Efficiency and sustainability of land-resource use on a small island - Keigo Noda; Akiko Iida; Satoshi Watanabe; Kazutoshi Osawa (Environmental Research Letters, 2019)
Land resources are essential for humans to survive, and different methods of land- resource use depend largely on the local natural context and society. Here we propose a method to assess land-resource use in terms of efficiency and sustainability for three historical types of land-resource use in the Babeldaob Island, Republic of Palau: self-supply, resource development and nature conservation. Our proposed index of land-use efficiency makes comparisons possible among the types of land-resource use, considering both the natural and social conditions; land-use efficiency increased in the order of self-supply, nature conservation and resource development. At the same time, sustainability of land-resource use corresponded to population growth; when the population density was less or more than 15 capita km ^−2 , self-supply and nature conservation were the most sustainable, respectively.